THE LEARNERS’ PERCEPTIONS OF SPEAKING ENGLISH AT LIA PRAMUKA ENGLISH CLUB - Imtihan - Hanim (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
Abstract The research was conducted to investigate the learners’ confidence towards their speaking skill in English Club in LIA Pramuka, East Jakarta for 2 months focused on perceptions of learners about their confidence in speaking English. The participants involved were 3 participants of English Club members, who were representative about the issue that possessed self-confidence problem. The researcher used questionnaire, interview, observation and documents to collect the data. After experiencing their speaking practice there, the researcher investigated about some perceptions toward speaking activities. The results of this study showed that they could raise their motivation and confidence to speak English since many vocabularies were acquired as they faced listening activity firstly. Besides, they had no anxiety in expressing their ideas anymore although they felt lack of speaking ability. The last, they got new friends there to share many life experiences as it can raise their confidence to express with. Keywords: Speaking, Self-Confidence-English Club